Diagnostic efficacy of fractional flow reserve with coronary angiography in dual-source computed tomography scanner. Issue 1 (2nd January 2018) - Xia, Guozhi; Fan, Di; Yao, Xiaowei; Guan, Gongchang; Wang, Junkui
Abstract: Objective: The management of patients with intermediate coronary lesions is a major clinical issue. Fractional flow reserve (FFR) is considered the gold criterion for the assessment of ischaemic stenosis, but it requires an invasive procedure. Coronary computed tomography angiography (CTA) for fractional flow reserve (FFRCT ) is a novel noninvasive alternative for the diagnosis of ischaemic lesions. The aim was to determine the diagnostic efficacy of FFRCT for ischaemic coronary artery stenosis lesions of intermediate severity. Methods: A total of 129 patients underwent 64-row dual-source CTA and invasive coronary angiography (ICA). In all, 156 vessels were identified as intermediate-grade coronary artery stenosis by subsequent ICA, defined as a maximum diameter reduction of 50%–70%. The FFR was also measured during ICA. FFRCT was computed from the three-dimensional dual-source CTA model and coronary flow dynamics data. Results: Per-patient diagnostic sensitivity, specificity, positive predictive values, negative predictive values and accuracy of FFRCT amounted to 89.2%, 81.5%, 66.0%, 94.9% and 83.7%, respectively; and 86.9%, 73.6%, 58.0%, 93.1% and 77.6% on the per-vessel basis, respectively. FFRCT and FFR showed a good positive correlation. Bland–Altman analysis displayed good concordance between FFRCT and FFR. The receiver operating characteristic curve revealed that the area under the curve of FFRCT was 0.918 (95% confidence interval 0.849–0.986) on the per-patient analysis and 0.916 (95% confidence interval 0.863–0.969) on per-vessel analysis, respectively. Conclusions: FFRCT is featured by moderate accuracy in discriminating lesions of intermediate coronary artery stenosis that cause myocardial ischaemia. Impact statement: How to treat intermediate coronary stenosis represents a major clinical issue. FFRCT has recently emerged as a novel noninvasive method evaluating ischemic lesions. In this study, we defined such lesion as 50–70% diameter stenosis. We designed the study to assess the diagnostic efficacy of FFRCT both at per-vessel level and at per-vessel levels for ischemic lesions.